2013
DOI: 10.1021/jp405147h
|View full text |Cite
|
Sign up to set email alerts
|

Hydrated Alkali Metal Ions: Spectroscopic Evidence for Clathrates

Abstract: The origin of enhanced abundances for some hydrated alkali metal ions, M(+)(H2O)n, where M = Cs, Rb, K, Na, and Li with between 17 and 21 water molecules attached was investigated with infrared photodissociation (IRPD) spectroscopy and by blackbody infrared radiative dissociation (BIRD) at 133 K. The abundances of clusters of Cs(+), Rb(+), and K(+) with 18 and 20 water molecules are anomalously high compared to the corresponding clusters of Na(+), and Li(+) with 20 water molecules has only a slightly enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
67
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 86 publications
4
67
0
Order By: Relevance
“…In this paper, we contrast the behavior of the n = 20 hydrates of the H 3 O + and Cs + ions, both of which are preferentially generated in the M + (H 2 O) n cluster ion distributions (i.e., are magic numbers) and are thought to be based on a pentagonal dodecahedron motif (12 interconnected H-bonded pentagons). An important difference between these ions is that H 3 O + is predicted to reside on the surface of the cage (6,8,26), whereas Cs + is sequestered in its interior (27,28). We follow the evolution of the bands in the perdeuterated isotopologues, Cs + (D 2 O) 20 and D 3 O + (D 2 O) 20 , and find strong support for the earlier assignment of the spectral signature of the embedded H 3 O + ion.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…In this paper, we contrast the behavior of the n = 20 hydrates of the H 3 O + and Cs + ions, both of which are preferentially generated in the M + (H 2 O) n cluster ion distributions (i.e., are magic numbers) and are thought to be based on a pentagonal dodecahedron motif (12 interconnected H-bonded pentagons). An important difference between these ions is that H 3 O + is predicted to reside on the surface of the cage (6,8,26), whereas Cs + is sequestered in its interior (27,28). We follow the evolution of the bands in the perdeuterated isotopologues, Cs + (D 2 O) 20 and D 3 O + (D 2 O) 20 , and find strong support for the earlier assignment of the spectral signature of the embedded H 3 O + ion.…”
mentioning
confidence: 55%
“…Two reported minimum energy structures (29) of the metal ion cage are displayed in Fig. 5 along with the corresponding harmonic predictions (note that nondodecahedral structures have also been shown to be nearly isoenergetic (27,30) and high-level ab initio searches have yet to be performed on this system). Both arrangements have 10 AAD type molecules colored in orange.…”
Section: Resultsmentioning
confidence: 99%
“…Although the structural origin of the magic number cluster stabilities is unknown, infrared photodissociation studies have suggested that complex clathrate structures may form for clusters of this size, which optimize hydrogen bonding and ultimately lead to enhanced stability. 21,53,54 …”
Section: Resultsmentioning
confidence: 99%
“…The spectra for clusters with n ≥ 162 have a feature centered at ∼3704 cm –1 characteristic of three-coordinate AAD (acceptor–acceptor–donor) water molecules. 53,54,5660 The frequency of these oscillators depends on the charge state of the hydrated ion, the extent of hydration and to a lesser extent, the size of the ion. 61,62 The intensity of this band increases for n = 182 and 218, indicating that the surface of these clusters is populated with an increasing number of AAD water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…55−59 There is a strong ADD stretch in the spectra of Cs + (H 2 O) 20 and some other alkali metal ions that is indicative of clathrate structures. 58 Patterning of Water Molecules at Long Distances. A free O−H band is commonly observed in the spectra of hydrated ions.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%